The implementation process of decentralization of health services: a qualitative perspective from Sudan - Noory, Bandar; Hassanain, Sara; Kassak, Kassem (Frontiers in Public Health, 2024)
Abstract Background: Health system reforms initiatives have adopted decentralization as a key trend, where its implementation process and outcome could be subject to various influences, including economic forces, political dynamics, and ideological factors. Comprehnding and carefully examining the implementation phase of decentralization and its consequences to achieve desired outcomes is crucial. Notably, this phase is often considered the weakest aspect of policy reforms, especially in developing countries. Therefore, this study aimed at exploring and analyzing the implementation phase of decentralization and its implications, as essentials for achieving intended goals. The study objectives evolved around examining the entire decentralization as a multifaceted social and political process in Khartoum State, Sudan from its early stages of decision-making, policy formulation and implementaion process and the influencing contextual factors. Methods: This was an exploratory qualitative study that employed in-depth interviews for gathering perspectives of healthcare providers and policymakers, semi-structured observations, and thematic analysis. The study utilized Grindle's (1980) framework for analysis. Findings: This study revealed a political nature of decision-making, with a top-down approach to the implementation which also lacked stakeholder involvement. It showed a lack of transparency, official documentation, and a proper handover procedures from the ministry of health to the devolved hospitals during the implementation process. A conflict of interest between the federal and the state level was also reported. It is important to note that this process occurred within the context of structural adjustment program schemes, which had already empowered the private sector in Sudan. Conclusion: This study documented the process of implementation and its influencing factors. The study recommended reforming the decentralization policy through consultative stakeholder involvement and by implementing a concurrent responsibility paradigm that divides authority between the federal and state levels.